Analisis greenwashing pada LSM menggunakan teori dan konsep sustainable management - Supriatno (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Greenwashing is a practice in which businesses or companies present false or misleading information about their sustainability initiatives for marketing purposes. This occurs when companies communicate positive environmental actions while hiding negative ones, creating a misleading impression of overall environmental performance. Greenwashing can occur through two actions: falsification (active deceit) and information selection (passive deceit). Information selection involves strategically choosing environmental communication content to eliminate negative information, while falsification involves creating false communication content. To avoid greenwashing, parameters such as data transparency, equal treatment, environmental focus, water efficiency, carbon footprint, waste packaging, and fair wages can be analyzed for an entity. Additionally, guidelines from the United States Federal Trade Commission (US-FTC) can also help differentiate between greenwashing practices and sustainable practices. However, in certain cases such as the Lindungi Hutan crowdfunding platform, there are several issues hindering environmental conservation efforts. The crowdfunding scheme used does not check the background of companies or individuals donating, allowing donations to come from businesses that have negative impacts on the environment. Additionally, the lack of annual public reports reduces transparency and accountability in fund management. Although this platform has various activities for environmental conservation, the effectiveness and impact of these activities are not well disclosed. Furthermore, claims from donors about their participation in environmental care programs are not aligned with the sustainability principles that should be followed. In conclusion, companies should focus on internal improvements and adhere to sustainability principles to avoid greenwashing. Additionally, crowdfunding platforms like Lindungi Hutan need to enhance transparency, accountability, and the effectiveness of their programs to ensure a real contribution to environmental preservation.